Snow : a scientific and cultural exploration - Whittell, Giles (Atria Books, 2019)
Go on an extraordinary journey across centuries and continents to experience the wonders of snow; from the prehistoric humans that trekked and even skied across it tens of thousands of years ago to the multi-billion-dollar industry behind our moving, making, and playing with snow. Blending accessible writing with fascinating science, Giles Whittell explores how snow dictates where we live, provides us with drinking water, and has influenced countless works of art and more. Whittell also uncovers compelling mysteries of this miraculous substance, such as why avalanches happen, how snow saved a British prime minister<U+2019>s life, where the legend of the yeti comes from, and the terrifying truth behind the opening ceremony of the 1960 winter Olympics. Filled with in-depth research and whip-smart prose, Snow is an eye-opening and charming book that illuminates one of the most magnificent wonders of nature.